Canine-assisted interventions : a comprehensive guide to credentialing therapy dog teams - Binfet, John-Tyler, 1964-; Hartwig, Elizabeth Kjellstrand (New York : Routledge, 2019)
Covering principles of therapy dog team training, assessment, skills, and ongoing monitoring, Canine-Assisted Interventions provides guidance on the most evidence-based methods for therapy dog team welfare, training, and assessment. The authors offer a linear approach to understanding all aspects of the screening, assessment, and selection of dog-handler teams by exploring the journey of dog therapy teams from assessment of canines and handlers to the importance of ongoing monitoring, recredentialing, and retirement. In addition to reviewing key findings within the field of human-animal interactions, each chapter emphasizes skills on both the human and dog ends of the leash and makes recommendations for research-informed best practices. To support readers, the book culminates with checklists and training resources to serve as a quick reference for readers. This book will be of great interest for practitioners, in-service professionals, and researchers in the fields of canine-assisted interventions and counseling.
"Covering principles of therapy dog team training, assessment, skills, and ongoing monitoring, this professional text provides guidance on the most evidence-based methods for therapy dog team welfare, training, and assessment. The authors offer a linear approach to understanding all aspects of the screening, assessment, and selection of dog-handler teams by exploring the journey of dog therapy teams from assessment of canines and handlers to the importance of ongoing monitoring, recredentialing, and retirement. In addition to reviewing key findings within the field of human-animal interactions, each chapter emphasizes skills on both the human and dog ends of the leash and makes recommendations for research-informed best practices. To support readers, the book culminates with checklists and training resources to serve as a quick reference for readers. This book will be of great interest for practitioners, in-service professionals, and researchers in the fields of canine-assisted interventions and counseling"--
10 Future Directions in Canine-Assisted InterventionsScenario; Best Practices for CAI Teams; Future Directions for CAI Organizations; Future Directions in CAI Research; Conclusion; Appendix A: Canine-Assisted Intervention Team Screening Form; Appendix B: Canine Health Screening Form; Appendix C: Canine-Assisted Counseling Skills Checklist; Appendix D: Canine-Assisted Intervention Team Assessment; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health; Psychiatric service dogs; Dogs -- Therapeutic use; Dogs -- Training